A Biomechanical Study on Laminectomy and Dekyphosis for Thoracic Ossification of the Posterior Longitudinal Ligament. (3rd November 2013) - Okayama, Tadaki; Murakami, Hideki; Demura, Satoru; Kawahara, Norio; Tomita, Katsuro; Tsuchiya, Hiroyuki
Abstract : We have successfully employed two-step circumspinal decompression for the treatment of thoracic OPLL. In the first step, laminectomy is performed according to the ossified lesion, and then correcting fixation of kyphosis (dekyphosis) is performed using instrumentation. In this study, we reconstructed the first step by a FEM. A commercially available FEM of the human body, THUMS, was used for the modeling of the operative procedure. The spinal cord and OPLL were incorporated into this model. After applying imposed displacement to OPLL, mechanical stress on the spinal cord was measured before or after posterior decompression at the occupying rates in the spinal canal between 0 and 70% in this model. When the occupancy rate was greater than 60%, the stress decreased after decompression compared to before decompression. The stress decreased by up to 52.3%. For reconstruction of dekyphosis, the change in the stress was analyzed after imposed displacement by which the spine was decreased: the cobb angle decreased by 10 degrees between T7 to T11. As a result, the stress further decreased by 14.6%. The present study proved the usefulness of posterior decompression and dekyphosis in order to reduce the pressure of the spinal cord in circumspinal decompression.